2016
DOI: 10.4103/2230-8210.192927
|View full text |Cite
|
Sign up to set email alerts
|

Neck height ratio is an important predictor of metabolic syndrome among Asian Indians

Abstract: Background and Aims:The predictive potential of neck circumference (NC) based indices (a measure of upper body fat distribution) for predicting metabolic syndrome (MetS) and its components among Indians is not known. This study aimed to evaluate the role of NC and neck height ratio (NHtR) as independent predictors of MetS and its components as compared to traditional anthropometric indices.Materials and Methods:A total of 451 individuals from 867 screened individuals, 30–80 years age, without any co-morbid sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
(33 reference statements)
4
22
1
4
Order By: Relevance
“…Kumar et al [18] examined the relationship between NC and metabolic syndrome among Indians, and found that compared with those without the syndrome, more people with metabolic syndrome had abnormal NC. Other workers also reported a higher mean NC in people with metabolic syndrome [25].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Kumar et al [18] examined the relationship between NC and metabolic syndrome among Indians, and found that compared with those without the syndrome, more people with metabolic syndrome had abnormal NC. Other workers also reported a higher mean NC in people with metabolic syndrome [25].…”
Section: Discussionmentioning
confidence: 81%
“…We found no correlation between NC and WHtR in this study. Other workers also found significant correlation between NC and indices of general and central obesity, blood pressure and blood glucose [11,17,21,25,26]. Additionally, some workers also found correlation between NC and other metabolic parameters such as serum total cholesterol, high density lipoprotein (HDL-C), triglycerides, C-reactive protein and insulin resistance [26].…”
Section: Discussionmentioning
confidence: 94%
“…Respecto a los indicadores índice cintura/talla, porcentaje de tejido adiposo e índice cintura/cuello, no existen parámetros de referencia a nivel nacional, y menos en una población similar a la de este estudio. Esta situación da cuenta de la necesidad de generar puntos de corte para la población Chilena, debido a la alta proporción de trabajadores que presentaron mediciones por sobre los puntos de corte propuestos en estudios con población similar 19,26 .…”
Section: Resultsunclassified
“…Otro indicador utilizado es el perímetro de cuello, el cual ha surgido como un método de bajo costo, fiable, no invasivo, fácil de reproducir y eficiente para la identificación de obesidad y riesgo cardiovascular en niños, adolescentes y adultos, para quienes incluso se han propuesto puntos de corte 15,16,17,18 . Es más, estudios recientes proponen utilizar el indicador cuello/talla, como una forma de corregir la influencia de la estatura entre sujetos, para el diagnóstico de riesgo cardiovascular 19 .…”
Section: Introductionunclassified
“…Several studies have been conducted in USA [21,25], Europe [26], Asia [27][28][29], Latin America [30], and Middle-East [31] have reported that NC has a direct relation with the blood pressure in adults. Even though, Servan et al [32] and Lou et al [33], revealed that higher NC has no correlation with higher blood pressure or the risk of HTN in adults. Moreover, Ozkaya et al [34] reported that NC is positively associated with systolic and diastolic blood pressure among Turkish men, but the same result was not seen in women.…”
Section: Introductionmentioning
confidence: 98%